Concepts and methods in modern theoretical chemistry : electronic structure and reactivity - Ghosh, Swapan Kumar; Chattaraj, Pratim Kumar (CRC Press, 2013)
"Written for students at advanced undergraduate and graduate levels, this book focuses on the electronic structures and reactivities of atoms and molecules. It begins with a general overview of topics and trends in theoretical chemistry including crystal engineering and computer-aided molecular design, then explores the more popular and successful quantum chemical techniques in use today. It pays particular attention to modern trends in the field. Techniques discussed include ab initio methods, density functional theory, and many body theory. It concludes with a discussion of other miscellaneous aspects of quantum chemistry such as electron correlations, molecular electronics, and reaction dynamics. Covers all the major areas of research in theoretical chemistry, particularly modern trends. Helps reestablish breadth of knowledge in the field after years of focused research. Timely, as the field has proliferated and diffused away from its core. Includes rigorous theoretical foundations as well as applications of vital chemical significance"-- Vydavatelská anotace
Keywords: teoretická chemie; chemická reaktivita; reakční kinetika; přenos elektronů; kvantová chemie; elektrochemie; theoretical chemistry; chemical reactivity; reaction kinetics; electron transfer; quantum chemistry; electrochemistry; sborníky; papers of several authors